2006
DOI: 10.1007/s11136-006-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

Constructing an Index for the Subjective Well-being Under Neuroleptics Scale (SWN), short form: Applying structural equation modeling for testing reliability and validity of the index

Abstract: Structural equation modeling (SEM) has been widely used in psychology and sociology for testing validity of measurement instruments. However, this statistical technique has so far played minor role in quality-of-life research. The main objective of this paper is to demonstrate the potential of SEM for constructing and testing the validity of a Subjective Well-being under Neuroleptics (SWN) index for patients with schizophrenia. For these purposes, data from the GEO study (Gesundheitsökonomische Evaluation von … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…If the health domains (latent factors) were highly correlated in the first‐order factor model, a second‐order factor model would provide a more parsimonious and interpretable model. A second‐order factor model allowed us to test whether the hypothesized higher order factor accounted for the relations among lower order factors; and it further simplified the interpretations of the complex structures of the first‐order model (10). Hence, the last step was to test for the fitting of the second‐order factor model to assess whether the overall OHRQoL was well captured and represented by the four underlying hypothetical health domains.…”
Section: Methodsmentioning
confidence: 99%
“…If the health domains (latent factors) were highly correlated in the first‐order factor model, a second‐order factor model would provide a more parsimonious and interpretable model. A second‐order factor model allowed us to test whether the hypothesized higher order factor accounted for the relations among lower order factors; and it further simplified the interpretations of the complex structures of the first‐order model (10). Hence, the last step was to test for the fitting of the second‐order factor model to assess whether the overall OHRQoL was well captured and represented by the four underlying hypothetical health domains.…”
Section: Methodsmentioning
confidence: 99%
“…An 8-item version of the WHOQoL instrument was used to assess perceived well-being (38). This is a cross-culturally valid instrument for comprehensively assessing overall subjective well-being, yet is also very brief.…”
Section: Designmentioning
confidence: 99%
“…The SWN has five subscores (mental functioning, self-control, emotional regulation, physical functioning, and social integration), each consisting of four questions. The original SWN and SWN-K (short form) have shown sufficient internal consistency (Cronbach's α was 0.92 for the total score and 0.63 to 0.82 for the subscores, whereas the correlation of the short form total score with the long version was 0.98) [23,25]. It has been reported that the SWN scores are moderately correlated with symptomatology evaluations and its improvement is slightly related to improvement of psychopathology ( r = −0.20 to −0.37).…”
Section: Methodsmentioning
confidence: 99%